Lo Stalinismo nei manuali scolastici russi contemporanei: tre narrazioni a confronto tra politiche educative e modelli interpretativi - Alessandro Farsetti (eSamizdat)
This article aims to reflect on the different historical narratives about Stalin’s period in nowadays Russia, especially with reference to the versions promoted in history textbooks for schools. After a reconstruction of the current educational policies in Russia, three textbooks adopted for the year 2018/2019 have been analysed. From the one hand, we can see how Russian authorities aim to use history as a mighty tool to shape people’s identity: we propose the category of “ritual” to understand this use; on the other hand, the three narratives by Zagladin, Volobuev and Torkunov are very different and seem to prove the existence of a “relative” freedom in the writing of history, if compared to the period 2004-2012.